MONITORING AND EVALUATION OF THE ARABLE LANDS OF THE ANDIJAN REGION (Scientific journal of the Fergana State University, 2024)
The article analyzes changes in the structure of land resources, analyzes the state of land use in the Andijan region today, the territorial aspects of existing cultivated lands, highlights the negative consequences of reducing the expected area of cultivated land, increasing the level of salinity.